Biological and Ecological Traits of Terrestrial Arthropods in North-West Morocco - Elharche Hanae (Polish Society of Ecological Engineering (PTIE), 2022)
In order to understand the relationship between the biological characteristics of insects and their environment, an entomological study was conducted at 5 stations (agricultural and natural) in the region of northwest Morocco (Sidi Kacem) between March 2019 and September 2020. Three sampling techniques were used (sweep nets, pitfall traps, and sight hunting). The inventory of insect species captured by these different methods in the various stations reveals the presence of 105 species distributed among 7 orders belonging to 35 families. According to the results, the presented adaptive parameters such as diet, flying ability, body size, and humidity sensitivity of the species showed that predators, macropterous, small size, and hygrophilic species are more frequent.